Emotion recognition by exploiting temporal resolution of EEG signals using transformation and learning methods - Uddin, Md.Tousif; Hossain, Mohammed Imaad; Khan, Shakik; Hoque, Tajwar-ul; Ahsan, Md.Jabid (Brac University, 2021)
Cataloged from PDF version of thesis.